Carriers and Sources of Magnetopause Current: MMS Case Study. Issue 7 (17th July 2018) - Dong, X.‐C.; Dunlop, M. W.; Wang, T.‐Y.; Cao, J.‐B.; Trattner, K. J.; Bamford, R.; Russell, C. T.; Bingham, R.; Strangeway, R. J.; Fear, R. C.; Giles, B. L.; Torbert, R. B.
Abstract: We investigate the current carriers and current sources of an ion scale tangential magnetopause current layer using the Magnetospheric Multiscale four spacecraft data. Within this magnetopause current layer, ions and electrons equally contribute to the perpendicular current, while electrons carry nearly all the parallel current. The energy range of all these current carriers is predominantly from middle to high (>100 eV), where particles with higher energies are more efficient in producing the current. By comparing each term, two‐fluid magnetohydrodynamic (MHD) theory is able to describe the current sources to a large degree because the sum of all the perpendicular currents from MHD theory could account for the currents observed. In addition, we find that the ion diamagnetic current is the main source of the total perpendicular current, while the curvature current can be neglected. Nevertheless, ions and electrons both carry comparable current due to the redistribution of the electric field and show features beyond the classic Chapman‐Ferraro model, particularly on the front side of the boundary layer where the electric field reversal is most intense. We also show a second, comparative event in which ions do not satisfy MHD theory, while the electrons do. The small‐scale, adiabatic parameter (square of curvature radius/gyroradius) supports our interpretation that this second event contains ion scale substructure. We suggest that comparing the predicted MHD current with plasma current can be a good method to judge whether the MHD theory is satisfied in each specific circumstance, especially for high‐precision Magnetospheric Multiscale data. Key Points: Identification of the current carriers and sources within the magnetopause boundary layer is made The ion diamagnetic current is found to be the main source of the perpendicular current Two‐fluid MHD theory is shown to hold for an ion gyroradius scale boundary layer, while it is partly violated for a more complex structure